Concomitant intestinal malrotation and Crohn's disease: a rare and surgically challenging anomaly. Issue 4 (12th April 2022) - Silverman, Jacob; Salwen, Benjamin; Goren, Idan; White, Ian
Abstract: Crohn's disease (CD) is a chronic inflammatory bowel disease characterized by transmural inflammation occurring anywhere along the gastrointestinal tract. Intestinal malrotation is an embryological error resulting in an abnormal gut anatomy. Although these two conditions rarely present concurrently, it is important to identify their presence, which is challenging due to their nonspecific, overlapping symptoms. Here, we present two patients with concomitant CD and intestinal malrotation. Both patients' conditions required surgical intervention, which was complicated due to their unique anatomy. Clinicians should be aware of the potential pit-falls that may occur due to the anomaly and thus require a full understanding of the anatomy.